ASSESSMENT OF THE ENVIRONMENTAL EFFECTS OF STREET TRADING IN AWKA - Aniedo, Chimezie; Egbuna, Onyinyechi K.; Alom, Anselem Chukwuma (FUDMA JOURNAL OF SCIENCES, 2025)
Street trading constitutes a pervasive economic activity in Nigerian urban centers, particularly in Awka, Anambra State. Its prominence is largely attributed to rural-to-urban migration, where individuals seek improved livelihoods and opportunities. In the absence of formal employment, many resort to informal street strading as a survival strategy. While this practice contributes to local economies and offers socio-economic resilience for marginalized groups, it also introduces substantial environmental and spatial challenges. This study critically examines the environmental and socio-spatial implications of informal street trading in Awka town. Adopting a mixed-methods approach, the research integrates semi-structured questionnaires, direct field observation, and in-depth interviews to generate a comprehensive understanding of the issue. Data were collected from 380 respondents, comprising traders, motorists, cyclists, and consumers across key informal commercial corridors. Quantitative findings indicate widespread urban effects, including solid waste accumulation, drainage obstruction, traffic congestion, and public health risks. Qualitative insights delve deeper into the spatial behaviors and adaptive strategies of informal vendors, revealing nuanced informal governance systems and the dynamic negotiation of public space. The findings illustrate the dualistic nature of street trading—as a critical socio-economic mechanism and a source of urban dysfunction. The study advocates for integrated urban management strategies including the creation of formalized trading corridors, deployment of enhanced waste management systems, implementation of spatial regulation policies, and expansion of educational empowerment programs. These interventions are essential to harmonizing economic informality with structured spatial development, supporting Awka’s transition toward a more inclusive, resilient, and environmentally sustainable urban future.
Keywords: Street Trading; Socio-spatial; Urban environment; Waste Management; Pollution